Controls on reservoir quality in exhumed basins – an example from the Ordovician sandstone, Illizi Basin, Algeria. (February 2017) - English, Kara L.; English, Joseph M.; Bonnell, Linda M.; Lander, Robert H.; Hollis, Cathy; Redfern, Jonathan; Guirdham, Claire; Garnham, Jenny; Yahia Cherif, Rachida
Abstract: Petroleum exploration in many North African intracratonic basins targets Early Paleozoic sandstones as the primary reservoir objective. These sandstones are often characterized by highly variable reservoir quality (0.0001–1000 mD), and the ability to predict and selectively target areas of enhanced porosity and permeability is crucial to unlock the hydrocarbon potential. The objective of this study is to characterize the primary controls on reservoir quality in an Ordovician field in the Illizi Basin of Algeria through detailed core and petrographic analysis, and establish if variations in thermal history across the field have a material impact on reservoir quality. The best reservoir quality is observed in facies where primary intergranular porosity has been preserved in fine to coarse grained quartzarenites with less than 1% fibrous illite. These lithologies are most commonly found within the high-energy, tidally reworked, post-glacial facies sandstones of the uppermost Ordovician succession. Observed differences in quartz cement volume within compositionally and texturally similar samples from the southern and northern parts of the field are interpreted to reflect variations in thermal exposure due to deeper burial. This interpretation is supported by field-wide numerical modelling of sandstone diagenesis. This study indicates that subtle variations in thermal history can have a material impact on the spatial trends in reservoir permeability. Thermal history, therefore, is an important consideration in reservoir quality studies in exhumed basins where variations in present-day burial depth will be a poor guide for evaluating reservoir quality risk across a basin or play. Highlights: Integrated study linking petrographic observations with numerical modelling of diagenesis. Best reservoir quality found in high-energy, tidally reworked, post-glacial sandstones. Quartz cement volume and reservoir quality varies across the field within similar facies. Spatial variation in reservoir quality linked to variable thermal history across the field.